Feedback That Works How to Build and Deliver Your Message, Second Edition (French), 2nd Edition - Leadership, Center for Creative (Center for Creative Leadership, 2020)
Effective feedback, whether it's meant for your boss, your peers, or your direct reports, is built around three ideas. One, focus on the situation. Two, describe the other person's behavior you observed in that situation. And third, describe the impact that behavior had on you. The result is a message that is clear and that can inspire action and productive change.